2015
DOI: 10.1002/cnma.201500012
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed Ultrathin Aluminosilicate Nanotube–Poly(vinyl alcohol) Composite Membranes with Partial Alignment of Nanotubes

Abstract: The fabrication of ultrathin (300 nm) aluminosilicate nanotube-poly(vinyl alcohol) composite membranes with partial vertical alignment of the nanotubes (up to 33 %), by solution-casting methods on porous polymeric substrates, is reported. Ah igh loading (up to 60 vol %) of nanotubes is achieved. Ac omprehensive microstructural characterization of the membranes is performed by ac ombination of SEM, TEM, grazing-incidence wide-angle X-ray scattering measurements, and simulations. This investigation shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…AlSiNTs comprise a crystalline structural topology (Figure ) with an empirical formula of (HO) 3 Al 2 O 3 SiOH possessing a monodispersed pore size of approximately 1 nm with functionalizable interior surfaces . High dispersity makes AlSiNTs amenable to aqueous‐phase processing and compatible with hydrophilic polymeric materials, such as poly(vinyl alcohol) . Several computational studies have reported that AlSiNTs possess a Young's modulus of approximately 340 GPa and a shear modulus of 160 GPa .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…AlSiNTs comprise a crystalline structural topology (Figure ) with an empirical formula of (HO) 3 Al 2 O 3 SiOH possessing a monodispersed pore size of approximately 1 nm with functionalizable interior surfaces . High dispersity makes AlSiNTs amenable to aqueous‐phase processing and compatible with hydrophilic polymeric materials, such as poly(vinyl alcohol) . Several computational studies have reported that AlSiNTs possess a Young's modulus of approximately 340 GPa and a shear modulus of 160 GPa .…”
Section: Introductionmentioning
confidence: 96%
“…[26,27] High dispersity makes AlSiNTsa menable to aque-ous-phase processing and compatible with hydrophilic polymeric materials, such as poly(vinyl alcohol). [28,29] Several computationals tudies have reported that AlSiNTsp ossessaYoung's modulus of approximately 340 GPa and as hear moduluso f 160 GPa. [23][24][25]30] However,t hese calculations are based on ad efect-freec rystalline model,w hich is very likely to overestimate the actual mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl alcohol) (PVA) is by far the most used polymeric material since PVA/INT can be processed easily from aqueous solutions. In most cases, the mechanical and optical properties of the resulting composite are enhanced, whether in film [84,[128][129][130][131], fiber [132] or membrane form [133][134][135] (Figure 7a). Beyond PVA, INT has been incorporated in a wide variety of polymer matrix (Table 3) either for nanotube-reinforced nanocomposites [90,96,100,138,143,149,150] with anisotropic structural properties (Figure 7b) [93,94,97,136,137,144,148,151,152], fabrication of hierarchical porous structures [139][140][141][142] or the encapsulation/sustained-release of biomolecules for medical applications (Figure 7c) [153][154][155][156][157][158][159].…”
Section: Applicationsmentioning
confidence: 99%
“…In the initial development of MMMs, only nearly spherical microporous materials were used as fillers [26,31]. In recent years, low-dimensional (1D and 2D) porous materials, such as nanotubes (1D) [32][33][34][35] and layered porous materials (2D) [36][37][38], have been regarded as emerging filler materials. Layered porous materials could potentially outperform near-spherical ones for use as filler in MMMs, for two reasons.…”
Section: Introductionmentioning
confidence: 99%